Effects of increasing meat and bone meal on finishing-pig growth performance - Gottlob, R.O.; Hastad, C.W.; Lawrence, K.R.; Groesbeck, C.N.; Goodband, Robert D.; Tokach, Michael D.; DeRouchey, Joel M.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 156 finishing pigs (72 barrows and 84 gilts, initially 110 lb) were used to determine the effects on growth performance of increasing meat and bone meal. Pigs were housed in an environmentally regulated finishing building, with two pigs per pen. There were six pens of barrows and seven pens of gilts per treatment. Pigs were blocked by initial weight and sex, and then allotted to one of six dietary treatments. The dietary treatments were based on corn-soybean meal, were formulated on a true-ileal-digestible (TID) lysine basis, and were fed in three phases. In each phase, diets contained 0, 2.5, 5.0, 7.5, 10.0, or 12.5% porcine meat and bone meal. The diets were formulated to 0.85, 0.70, and 0.57% TID lysine in phases 1, 2, and 3, respectively, slightly less than the pig’s anticipated requirements, so that if the amino acid digestibility of meat and bone meal was different than typical values, changes in growth performance could be observed. Increasing meat and bone meal increased ADG (quadratic, P<0.02), decreased ADFI (linear, P<0.02), and improved F/G (quadratic, P<0.01). Pigs fed 2.5 or 5.0% meat and bone meal had the best ADG and F/G; as meat and bone meal increased to higher concentrations, however, ADG and F/G decreased and were similar to those of pigs fed the control diet. Because the diets were formulated with slightly less than the pig’s anticipated requirements, the results suggest that the meat and bone meal used was relatively high quality and contained greater digestible amino acids than expected. These results suggest that porcine meat and bone meal is a suitable replacement for soybean meal.
Keywords: Swine; Meat and bone meal; Finishing pigs; Pigs